Anti‐migraine Calcitonin Gene–Related Peptide Receptor Antagonists Worsen Cerebral Ischemic Outcome in Mice. Issue 4 (7th August 2020) - Mulder, Inge A.; Li, Mei; de Vries, Tessa; Qin, Tao; Yanagisawa, Takeshi; Sugimoto, Kazutaka; van den Bogaerdt, Antoon; Danser, A. H. Jan; Wermer, Marieke J. H.; van den Maagdenberg, Arn M. J. M.; MaassenVanDenBrink, Antoinette; Ferrari, Michel D.; et al.
Abstract : Objective: Calcitonin gene–related peptide (CGRP) pathway inhibitors are emerging treatments for migraine. CGRP‐mediated vasodilation is, however, a critical rescue mechanism in ischemia. We, therefore, investigated whether gepants, small molecule CGRP receptor antagonists, worsen cerebral ischemia. Methods: Middle cerebral artery was occluded for 12 to 60 minutes in mice. We compared infarct risk and volumes, collateral flow, and neurological deficits after pretreatment with olcegepant (single or 10 daily doses of 0.1–1mg/kg) or rimegepant (single doses of 10–100mg/kg) versus vehicle. We also determined their potency on CGRP‐induced relaxations in mouse and human vessels, in vitro. Results: Olcegepant (1mg/kg, single dose) increased infarct risk after 12‐ to 20‐minute occlusions mimicking transient ischemic attacks (14/19 vs 6/18 with vehicle, relative risk = 2.21, p  < 0.022), and doubled infarct volumes ( p  < 0.001) and worsened neurological deficits (median score = 9 vs 5 with vehicle, p  = 0.008) after 60‐minute occlusion. Ten daily doses of 0.1 to 1mg/kg olcegepant yielded similar results. Rimegepant 10mg/kg increased infarct volumes by 60% after 20‐minute ischemia ( p  = 0.03); 100mg/kg caused 75% mortality after 60‐minute occlusion. In familial hemiplegic migraine type 1 mice, olcegepant 1mg/kg increased infarct size after 30‐minute occlusion (1.6‐fold, p  = 0.017). Both gepants consistently diminished collateral flow and reduced reperfusion success. Olcegepant was 10‐fold more potent than rimegepant on CGRP‐induced relaxations in mouse aorta. Interpretation: Gepants worsened ischemic stroke in mice via collateral dysfunction. CGRP pathway blockers might thus aggravate coincidental cerebral ischemic events. The cerebrovascular safety of these agents must therefore be better delineated, especially in patients at increased risk of ischemic events or on prophylactic CGRP inhibition. ANN NEUROL 2020;88:771–784